Influences of Emotion on Driving Decisions at Different Risk Levels: An Eye Movement Study - Zhang, Xiaoying; Chang, Ruosong; Sui, Xue; Li, Yutong (Frontiers in Psychology, 2022)
Abstract：In order to explore the influences of emotions on driving decisions at different risk levels, we induced the drivers' three emotions (neutral emotion, traffic-related negative emotion, and traffic-unrelated negative emotion) by videos, and recorded eye movement during the driving decision at three risk levels (high-risk, low-risk, and no-risk). We found that emotions influence driving decisions about whether to slow down. Compared with neutral emotion, traffic-related negative emotion led to an increase in the number of deceleration decisions, and the higher the risk, the more the number of decelerations. The first round visual processing time of the risk area was shorter in two negative emotional states than that in the neutral emotional state. However, the total visual processing time of the risk area was shorter only in the traffic-related negative emotional state than that in the neutral emotional state. The less time drivers gazed at the risk, the faster they made driving decisions. This study proved that the traffic-related negative emotion induced by the traffic accident scene and warning education clip video led to the increase of drivers' deceleration decisions and faster response, which is a reference for drivers' safety education and training.